2019
DOI: 10.1021/acs.jchemed.9b00107
|View full text |Cite
|
Sign up to set email alerts
|

A Prelaboratory Framework Toward Integrating Theory and Utility Value with Laboratories: Student Perceptions on Learning and Motivation

Abstract: Laboratory-based learning can be weakened by a lack of connection with underlying theory and limited contextualization to enhance motivation. To address these shortcomings, a framework for the development of web-based multimedia prelaboratory modules is proposed. The framework incorporates supportive information (content), utility value (context), multimedia design principles (design), and questions/explanatory feedback (formative assessment). On the basis of this framework, prelaboratory modules were develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
(108 reference statements)
2
24
0
Order By: Relevance
“…The resources in the current study were found to increase the preparation time of students who sought out alternative ways of studying before class, which is a consistent finding with that of Jolley et al (2016). Pre-laboratory activities have been claimed to address certain problems related to laboratory-based courses (Moozeh et al, 2019); thus, online resources integrated into pre-laboratory activities could offer solutions to some problems regarding laboratory-based instruction. However, the current study found that few students spent time on their pre-laboratory preparation.…”
Section: Preparation As An Integral Part Of Classroom Practicessupporting
confidence: 80%
See 1 more Smart Citation
“…The resources in the current study were found to increase the preparation time of students who sought out alternative ways of studying before class, which is a consistent finding with that of Jolley et al (2016). Pre-laboratory activities have been claimed to address certain problems related to laboratory-based courses (Moozeh et al, 2019); thus, online resources integrated into pre-laboratory activities could offer solutions to some problems regarding laboratory-based instruction. However, the current study found that few students spent time on their pre-laboratory preparation.…”
Section: Preparation As An Integral Part Of Classroom Practicessupporting
confidence: 80%
“…Quizzes and pre-lectures were used to present conceptual knowledge, whereas videos and simulations referred to the improving of skills and procedural knowledge. The prelaboratory categories mostly focused on experimental procedures on how to perform and experiment rather than purely theoretical considerations (Moozeh et al, 2019). However, in recent years, the distinction has been less apparent, and some studies have emphasized online resources to be used for both content and procedural practices (Agustian and Seery, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Engineering laboratories are key spaces for identity formation; they bridge the 'theory/practice divide', 6 enabling theory to be applied to engineering problem-solving and design, 7 as well as revealing the scientific basis of engineering artefacts 8 whilst engaging students in experiments and active learning. 9 Learning in an engineering laboratory tends to be more active than in classrooms and lecture halls and includes consolidating scientific and engineering concepts, 10 developing engineering design abilities 11 and nurturing professional and social skills.…”
Section: Why the Undergraduate Laboratory?mentioning
confidence: 99%
“…Enabling students' access to particular laboratories had 'an influence on identity development by allowing the students to recognise their admission to a specific community'. 19 The positive contribution of active learning in laboratories to engaging students' interest in engineering subject matter and in identity formation was recognised in a number of studies, 7,18 but many studies also pointed to negative experiences in engineering laboratories. Women students and underrepresented groups described themselves as 'isolated', 14 'side-lined' 35 or 'not participating fully'.…”
Section: Spatial Affordances For the Development Of Engineering Identitiesmentioning
confidence: 99%
“…By understanding the usefulness of the material, students were then more motivated to learn and accomplish their chemistry (Moozeh, Farmer, Tihanyi, Nadar, & Evans, 2019). Formative assessments were included at the end of the video without a time limit.…”
Section: Innovative In-lab Activitiesmentioning
confidence: 99%